A defamiliarising ‘scholarship of hope’: A youth subjectivity and schooling perspective - Fataar, A (South African Journal of Higher Education, 2011)
This article advances the notion of a ‘scholarship of hope’ in order to signpost one route into a generative approach to academic work. Such an approach has to proceed on the basis of a defamiliarising type of inquiry meant to challenge dominant understandings of our social world. I suggest that a defamiliarising scholarship of hope involves asking courageous and novel questions, applying methodological inventiveness, and the pursuit of the explanandum in unfamiliar spaces, accompanied by an eclectic box of analytical tools and descriptive languages. I offer this article as an example of such a scholarship of hope. It is based on a discussion of aspects of black youth subjectivity in relation to their school going. It is an attempt to unsettle predominant understandings of young lives and their school-based navigations. The article starts off with a discussion about what a scholarship of hope might entail. This is followed by some thoughts on the study of subjectivity in education. I then move to a consideration of young people’s school lives in the light of their rearranged social contexts, followed, finally, by a perspective on them in the post-apartheid turnover. The main argument of this article is that a scholarship of hope ought to be based on bringing understandings of excluded communities and their perspectives and knowledges to academic consciousness. Such a scholarship is also meant to inform the critical pedagogical work of educators in school classrooms and university lecture halls.